Asistanların elektrokonvulsif tedavi ile ilgili bilgi ve tutumları - (:unkn) unknown (My University, 2015)
AMAÇ: Bizim bilgilerimize göre, psikiyatri dışı hekim ve asistanların Elektrokonvulsif Tedavi (EKT) ile ilgili bilgi ve tutumları şimdiye kadar yeterince araştırılmamıştır. Psikiyatri dışı asistanların EKT ile ilgili bilgi ve tutumlarını incelemeyi ve dahili ve cerrahi bilim dallarındaki asistanları bu açıdan karşılaştırmayı amaçladık. YÖNTEM: Çalışmaya bir üniversite hastanesinden (119 dahili bilim, 57 cerrahi bilim) tıp fakültesi mezunu 176 asistan katıldı. Tüm katılımcılardan yazarların hazırladıkları anketi doldurmaları istendi. BULGULAR: Katılımcıların arasından 58 (%48,7) dahili bilim ve 32 (%56,1) cerrahi bilim asistanı daha önce bir EKT seansı izlemediklerini bildirdi. EKT tutumları açısından iki asistan grubu arasında istatistiksel bir farklılık yoktu (p>0.05). Cerrahi bilim asistanlarının akrabalarına EKT uygulanmasına onay verip vermeyeceklerinin sorgulandığı soruda diğer gruba kıyasla daha fazla onay vermeyeceklerini belirttiler (p=0.02). SONUÇ: Dahili ve cerrahi bilim asistanlarının EKT ile ilgili bilgi ve tutumları benzer görünüyordu. Her ne kadar asistanların EKT hakkında önemli miktarda bilgileri olsa da EKT ile ilgili tutumları daha önce literatürde hasta ve yakınları ile ilgili yapılmış çalışmalardakine benzerlik gösteriyordu. Çalışma sonuçları tıp fakültelerinde verilen eğitimin mezunlarının EKT ile ilgili tutumlarını geliştirecek şekilde düznelenmesine ihtiyaç olduğu şeklinde yorumlanabilir.

AIM: To determine the knowledge and attitudes of non-psychiatry residents about electroconvulsive therapy (ECT) and additionally to make a comparison between residents of medical sciences and surgical sciences. METHODS: The study consisted of 176 medical school graduates in their residency training (119 medical sciences, 57 surgical sciences) at a university hospital. All subjects are asked to fill a questionnaire prepared by the authors. RESULTS: Among all, 58 of the medical sciences residents (48.7%), and 32 of the surgical sciences residents (56.1%) had reported that they have never observed any ECT session. There was no statistically significant difference between the residents of the two groups in terms of theirs attitudes towards ECT (p>0.05). The residents of surgical sciences differed from the others only in their response to the question that sought answer whether they would agree to have any of their relatives to undergo ECT. They more often disagreed to this statement (p=0.02). CONCLUSIONS: The knowledge and attitudes of residents in medical, and surgical sciences about ECT seemed to be similar. Despite their significant amount of knowledge about ECT the residents showed similar attitudes towards it with the patients and their caregivers that were previously reported in the literature. Additionally, the results also suggest that current training in medical schools need a revision that would eventually improve attitudes of medical graduates towards ECT.
[Knowledge and attitudes of residents regarding electroconvulsive therapy]
Keywords: Davranış Bilimleri